Pemikiran Ibnu Khaldun Tentang Pendidikan Dan Relevansinya Dalam Sistem Pendidikan Kontemporer - Theodora Indah Jati; Rayi Ambarwati; Ratnasari Ratnasari; Tamrin Fathoni (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Ibn Khaldun, a prominent 14th-century Islamic scholar, offered groundbreaking ideas on education that continue to hold relevance in contemporary educational systems. His thoughts emerged from a broader context of Islamic scholarship, emphasizing the importance of knowledge acquisition for both individual and societal advancement. The purpose of this study is to examine Ibn Khaldun's educational philosophy and explore its relevance to modern education systems. Drawing on his magnum opus, Muqaddimah, this study delves into his concepts of the stages of learning, the role of the teacher, and the importance of experience alongside theoretical knowledge. The research employs a qualitative analysis of primary sources, with a focus on comparing traditional Islamic thought with modern educational theories. Findings suggest that Ibn Khaldun’s holistic approach to education (1)combining moral, intellectual, and practical (2)provides valuable insights for addressing current educational challenges, such as fostering critical thinking and adapting to the evolving demands of a globalized world. The study concludes that Ibn Khaldun’s educational philosophy remains highly relevant, particularly in terms of cultivating well-rounded individuals and promoting a dynamic, adaptable educational system.